2020
DOI: 10.15273/pnsis.v50i2.10002
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating out-planting success and mycorrhizal status of endangered Geum peckii Pursh (Rosaceae), the Eastern Mountain Avens, in Nova Scotia

Abstract: Geum peckii (Rosaceae), the Eastern Mountain Avens, is a small herbaceous plant that is listed as endangered federally and provincially. In Canada, this species is found in bogs on Brier Island and Harris Lake, Digby County, Nova Scotia. The only other population outside of Canada is in New Hampshire (USA). To enhance conservation research of this species, a seed sample from the native species seed bank at Acadia University was used to establish a plant tissue culture of G. peckii plants. Survival of out-plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…Although it is difficult to tease apart the potential influence of these two scenarios, the notion of fungi being associated with the mycobiome of G. peckii is of some merit. For instance, Cryptodiaporthe aubertii, which was found at all five sites observed during our study, was also found in aseptically grown G. peckii transplants, which were out planted to a comparable bog habitat on Digby Neck at which G. peckii had not been observed previously [15,23]. Despite the possibility of G. peckii having a core set of fungal endophytes, our study found that disturbed sites had lower fungal richness than the pristine site.…”
Section: Trends In the Endophytic Fungi From Geum Peckiisupporting
confidence: 71%
See 3 more Smart Citations
“…Although it is difficult to tease apart the potential influence of these two scenarios, the notion of fungi being associated with the mycobiome of G. peckii is of some merit. For instance, Cryptodiaporthe aubertii, which was found at all five sites observed during our study, was also found in aseptically grown G. peckii transplants, which were out planted to a comparable bog habitat on Digby Neck at which G. peckii had not been observed previously [15,23]. Despite the possibility of G. peckii having a core set of fungal endophytes, our study found that disturbed sites had lower fungal richness than the pristine site.…”
Section: Trends In the Endophytic Fungi From Geum Peckiisupporting
confidence: 71%
“…Of special note was the species Cryptodiaporthe aubertii, which was found as a G. peckii foliar endophyte at all sites. Intriguingly, this species has also been reported from the foliar tissues of G. peckii grown from seed in sterile tissue culture prior to ex situ planting in the Digby Neck bog habitat, where no G. peckii have previously been observed [15]. This fungus is a known endophyte and is possibly a latent saprophyte of Sweet Gale (Myrica gale), collected in bogs in Sweden and Russia [42,43].…”
Section: Known Ecologies Of Sordariomycetes Recovered From Geum Peckiimentioning
confidence: 82%
See 2 more Smart Citations